APPLICATION OF GRAPHENE OXIDE ON APTAMER-BASED BIOSENSOR DEVELOPMENT FOR AUTHENTICATION OF GELATIN - WIDADA, HARI; ROHMAN, ABDUL; JENIE, RIRIS ISTIGHFARI; SISMINDARI (International Journal of Applied Pharmaceutics, 2019)
Objective: The objective of this study was to perform aptamer selection using systematic evolution of ligands by exponential enrichment (SELEX) method which assisted by graphene oxide against target of porcine gelatin (non-halal gelatin). Methods: The aptamer selection was carried out using SELEX method without target immobilization. Selection of aptamer capable of binding porcine gelatin by applying grafen oxide (GO) was known as GO-SELEX. The selection process was initially carried out by incubation of single-stranded DNA (ssDNA) libraries targeting on porcine gelatin with the addition of graphene oxide. The selected ssDNA was then purified by several stages namely; symmetric PCR amplification, purification of products with DNA purification kits, asymmetric PCR amplification, and continued purification of DNA with native PAGE. The analysis of each stage was done by agarose gel electrophoresis. Results: the results showed that aptamer targeting porcine DNA could be selected. This was indicated by the results of DNA analysis using native polyacrylamide gel electrophoresis (PAGE) in which sharp separation band with a base length equivalent to the marker of the ssDNA library (about 80 base pair) was obtained. Conclusion: Aptamer targeting on porcine gelatin has been successfully developed using GO-SELEX method. GO can increase selectivity in developing aptamer which will be used as a biosensor to detect porcine gelatin. The method could be proposed as a standard of apatamer based method for porcine gelatin detection on halal products authentication.